Perlindungan Khusus Terhadap Anak Berhadapan Dengan Hukum - Syarifuddin, Syarifuddin; Salsabila, Athira; Lumban Gaol, Putriani; Fadila, Dwi (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2025)
The main function of the state in the legal system that prioritizes the defense and enforcement of human rights, especially children's rights, is the protection of children. Because they are the future of the country, children need extra attention to reach their full potential. Referring to Article 23 Paragraph 1 of Law No. 17/2016 concerning the Second Amendment to Law No. 23/2002 concerning Child Protection (PA Law), the State, Government, and Regional Governments are obliged to ensure the protection, maintenance, and welfare of children while still paying attention to the rights and responsibilities of parents, guardians, or other persons who are legally responsible for children. Children's basic rights to life, safety, growth and development and engagement are protected by each of these devices. However, there are still other practical problems, such as limited reach and lack of collaboration between local governments. To ensure that the child protection system functions fairly, comprehensively, and effectively, the right of children of criminal offenders to obtain legal protection and the right of child victims to obtain restitution must be a top priority. Increased public awareness, institutional coordination, and law enforcement are needed to create a comprehensive and sustainable child protection system in Indonesia.